PDGFR-β-Positive Perivascular Adventitial Cells Expressing Nestin Contribute to Fibrotic Scar Formation in the Striatum of 3-NP Intoxicated Rats - Tae-Ryong Riew (Frontiers in Molecular Neuroscience, 2018)
Perivascular cells expressing platelet-derived growth factor receptor beta (PDGFR-β) have recently been implicated in fibrotic scar formation after acute brain injury, but their precise identity and detailed morphological characteristics remain elusive. This study sought to characterize and define the cellular phenotype of vascular-associated cells expressing PDGFR-β in the striatum of rats treated with the mitochondrial toxin 3-nitropropionic acid (3-NP). In the control striatum, PDGFR-β-positive cells were invariably localized on the abluminal side of smooth muscle cells of larger caliber vessels, and demonstrated morphological features typical of perivascular fibroblasts. PDGFR-β expression increased and expanded to almost all vessels, including microvessels in the lesion core, at 7 days after 3-NP injection. The cells expressing PDGFR-β had ultrastructural features of fibroblasts undergoing active collagen synthesis: large euchromatic nuclei with a prominent nucleolus, well-developed rough endoplasmic reticulum (rER) with dilated cisterns and extracellular collagen fibrils. By 14 days, PDGFR-β-positive cells had somata located at a distance from the vasculature, and their highly ramified, slender processes overlapped with those from other cells, thus forming a plexus of processes in the extravascular space of the lesion core. In addition, their ultrastructural morphology and spatial correlation with activated microglia/macrophages were elaborated by three-dimensional reconstruction. Using a correlative light- and electron-microscopy technique, we found that the intermediate filament proteins nestin and vimentin were induced in PDGFRβ-positive fibroblasts in the lesion core. Collectively, our data suggest that perivascular PDGFR-β-positive fibroblasts are distinct from other vascular cell types, including pericytes and contribute to fibrotic scar formation in the lesion core after acute brain injury. Nestin and vimentin play critical roles in the structural dynamics of these reactive fibroblasts.